Halal purchasing: a qualitative in-depth interview towards small and medium food enterprises (SMFEs) - Nurulfaraiza, Ariffin; Veera Pandiyan, Kaliani Sundram; Mohd Hafiz, Zulfakar (Proceedings of the 11th International Conference on Business, Accounting, Finance and Economics (BAFE 2023), 2023)
The sourcing of raw materials poses a consistent obstacle for the majority of small and medium-sized food enterprises, primarily due to their inability to make purchases in large quantities compared to larger organizations. It encompasses a set of principles and guidelines designed to ensure the integrity and authenticity of halal products and services throughout the entirety of the value chain, a responsibility mandated for Muslims. This exploratory research paper is based on in-depth interviews to better understand the process of purchasing in Halal. A qualitative approach to data collection was undertaken using semi-structured in-depth interviews via case study. In addition to contending with a limited pool of suppliers for their products, these enterprises must also ensure that their chosen suppliers possess halal certification to fulfil the essential requirements. The findings provide insights into small and medium-sized food enterprises regarding the importance of engaging larger suppliers as sources for raw materials in the halal market. This approach ensures compliance with the highest standards of halal certification, potentially affording a competitive advantage within the global halal market.